Metabolic responses and performance in tennis with caffeine feeding - Farrauti, A. (1997)
A study was conducted among 16 tournament tennis players to investigate the effects of caffeine, in concentrations common in commercially available beverages, on metabolism and performance during a four-hour tennis match (with 30 minutes rest after 150 minutes). In two randomized double-blind tests, players ingested an orange-flavoured drink with 130 mg/l caffeine, or a placebo, at court changeover and during the break. In all subjects, urine caffeine concentrations remained below the doping limit. Sprint performance, hitting accuracy, perception ratings and playing success were not affected by caffeine. Nevertheless, in women (8 subjects), a higher energetic drive was measured after caffeine feeding and a corresponding better playing success. In conclusion, no definite metabolic benefits of caffeine were found when administered in commercially available doses. However, the data indicate that caffeine accelerates exercise adaptation after rest and may have specific ergogenic mental effects in women's tennis. Further studies are needed to verify these hypotheses.